The Effect Of Zakat On Income Disparity In Aceh Province - Oka Fadliansah; Suriani Suriani; Eddy Gunawan (Research Collaboration Community (RCC), 2021)
This study analyzes the effect of zakat funds, human development index, Gross Domestic Product, and poverty on income inequality in 21 districts/cities in Aceh Province. This study uses panel data from 21 districts/cities in Aceh Province for the 2010-2019 period. The results found the regression coefficient of zakat funds have a positive relationship with a significance level of 0.08, which means that an increase in zakat funds of 1 % will increase income inequality by 0.011 points. Then the human development index variable has a negative effect with a significant level of income inequality of 0.000, which means that each human development index increases by 1 %, it will reduce income inequality by 0.12 points. Furthermore, the poverty variable that can describe the role of income inequality, the results obtained have no effect on income inequality in 21 districts/cities of Aceh Province during the study period. Then the last variable is Gross Domestic Product which has a negative relationship with a significance level of 0.0049 on income inequality in 21 districts/cities in Aceh Province during the study period. The resulting regression coefficient is 0.011 %, which means that when the Gross Regional Domestic Product increases by 1 %, it will reduce income inequality by 0.011 points.